KEPEMIMPINAN TRANSFORMASIONAL DALAM PENDIDIKAN ISLAM YANG UNGGUL - Iqbal Hidayatsyah Noor; Dartim Dartim (Universitas Muhammadiyah Surakarta, 2021)
For the world of education, success in an educational leadership is determined from the analysis of management characteristics based on a systems approach: input, process and output. The output of an educational institution is school achievement resulting from the learning process and school management as a measure of quality. This system is strongly influenced by good leadership performance (transformational leadership). The presence of this paper is to be able to find a concept map so that the rational way of thinking on the influence of transformational leadership can be understood more easily. Then in this paper will also discuss how Islam views the concept of leadership in such a way